IDENTIFIKASI FAKTOR KEGAGALAN UJIAN BBQ PADA MAHASISWA TEKNIK INDUSTRI - annisa, annisa mulia rani (ReTII, 2019)
The Faculty of Engineering of the University of Muhammadiyah has provisions for every student to have abilities outside of academic ability, namely English language skills and the ability to read the Koran correctly and memorize the Quran and Alhadist. A provision for the ability to read the Quran and for the ability of the Quran is to be able to read the Quran according to recitation, the total number of Quran letters is 20 letters. The place to carry out the guidance of the Quran and its examinations is at the Al-Islam and Kemuhammadiyahan Laboratory (AIK Lab) But for the FT UMJ IT students there are 32% who have failed, therefore it will be analyzed through factor analysis to find out the cause of the failure of the BBQ exam using the factor analysis method. Mean square analysis is used in factor analysis where the mean square analysis received above 0.5. SPSS 16 software is used to process data in this study. The results obtained that students who took the BBQ exam more than 1 x was 32%, and the student was declared a failure. And seen from the students who did not succeed were 0% who had never participated in BBQ support activities and 100% had participated in BBQ support activities. The BBQ exam failure variables are Study, Motivation, Attention, Business, Health, and Background. Factor analysis testing using the Bartley test and Measure sample of adequate must meet the sig value of 0.04 and MSA 0.540. With these values ​​declared passed the test. But there is one variable that must be excluded because the MSA value is less than 0.5, namely health. Furthermore, the second stage of determining the factors with msa value for learning 0.69 motivation 0.55 attention 0.53 and background 0.52